(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Student attendance is considered one of the important indicators of the success of the learning process in schools. A decline in attendance can affect academic achievement, discipline, and students’ social development. This study aims to describe the school’s strategies to improve student attendance at SMA Nurul Khoir Jambi. The study uses a qualitative approach with a descriptive research type. The research subjects include the principal, classroom teachers, students, and parents who were selected purposively. Data were collected through in-depth interviews and documentation, while data were analyzed using the interactive model of Miles, Huberman, and Saldana with source documentation to ensure data validity. The research results indicate that low student attendance is influenced by internal factors of the students, pedagogical factors, as well as external factors related to parental involvement. The strategies implemented by the school include daily attendance monitoring, guidance through individual counseling, the application of positive discipline, and enhancing communication and collaboration with parents. Teachers, especially those responsible for the class, play an important role in early detection and student support, while the principal is involved in subsequent policy-making. The study concludes that collaborative, humanistic, and sustainable strategies can gradually improve student attendance